anonymous
  • anonymous
i need step by step in solving for X-Y 6x+2y=22
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
lgbasallote
  • lgbasallote
...is X-Y included in the equation?
anonymous
  • anonymous
yes
anonymous
  • anonymous
I mean No

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

lgbasallote
  • lgbasallote
...well you cant solve for x and y without a second equation
anonymous
  • anonymous
ok so it needs another equation how about 3x-10y=-12
lgbasallote
  • lgbasallote
you do systems of linear equations... 6x + 2y = 22 3x - 10y = -12 multiply the second equation by -2 6x + 2y = 22 -6x +20y = 24 22y = 46 11y = 23 y = 23/11 6x +46/11 = 22 6x = 22 - 46/11 6x = 196/11 x = 98/33
jhonyy9
  • jhonyy9
6x+2y=22 so to solve this for x and y you need again one equation with x and y - than if you have this second equation on first step you see that from 6,2 and 22 you can extracting the 2 like common factor so than from this equation you will get 2(3x+y)=2(11) ,so than you can divide both sides by 2 and will remain 3x+y=11 from this you will get that y=11-3x and now if you have the second equation so than this y=11-3x you need just to substitute inside second equation in the place of y and than will get one equation just with x ,so from this you can calcule the x and after you get the x value with this you can calcule easy the term of y ... hope so much that is understandably sure and easy good luck bye

Looking for something else?

Not the answer you are looking for? Search for more explanations.